Pricing Strategies and Demand Dynamics in Indigenous Micro-Textile Enterprises - Machela, Tsepo (International Review of Management and Marketing, 2025)
This study explores the pricing strategies employed by indigenous micro-textile enterprises in Durban, South Africa, and assesses their impact on consumer demand and business sustainability. Using an exploratory sequential mixed-methods approach, the research draws on qualitative interviews with 50 μ-entrepreneurs and a quantitative survey of 384 participants to uncover how pricing decisions are shaped by contextual constraints, cultural values, and firm-level strategic behaviours. The findings reveal that pricing practices vary significantly across three distinct tiers of micro-textile operations, with Tier Three businesses exhibiting informal and reactive pricing models, while Tier One enterprises engage in more structured, value-based strategies. Key challenges identified include high consumer price sensitivity, limited access to business development support, and the influence of unstructured entrepreneurial decision-making. The study also highlights the role of focus-based strategies, such as cost leadership and product differentiation, in enabling micro-enterprises to navigate competitive markets. Recommendations include strengthening pricing literacy, integrating digital tools, and enhancing the role of business incubators in supporting culturally grounded and market-responsive pricing models. These insights contribute to the broader discourse on inclusive marketing, informal entrepreneurship, and sustainable micro-enterprise development in emerging economies.